'Yes, that's the best': Short front vowel lowering in English today: Young people across the anglophone world are changing their pronunciation of vowels according to a change which started in North America. Issue 2 (12th December 2017) - Hickey, Raymond
Abstract : In different parts of the English-speaking world various vowel changes have been taking place in recent years, perhaps the most noticeable of which is the vowel lowering in words like DRESS and TRAP. This lowering would seem to have its origins some few decades ago in North America, probably in California and perhaps simultaneously in Canada. The shift, labelled here short front vowel lowering (SFVL), has spread quickly across the anglophone world and is found in locations as far apart as Ireland, South Africa and Australia. In each case where the change has been adopted there has been an adaptation of the change to local circumstances within the borrowing variety. The transmission of the change is also significant as the spread would seem not to be by direct speaker contact.